Oral salt and water versus intravenous saline for the prevention of acute kidney injury following contrast-enhanced computed tomography: study protocol for a pilot randomized trial - Swapnil, Hiremath; Knoll, Greg A; Kayibanda, Jeanne F; Fergusson, Dean; Chow, Benjamin J; Shabana, Wael; Murphy, Erin; Ramsay, Tim; James, Matthew; White, Christine A; Garg, Amit; Wald, Ron; et al. (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Although intravenous saline is the accepted prophylactic measure for the prevention of contrast- induced acute kidney injury, the oral route could offer an equivalent, practical, and cost saving approach. A systematic review of randomized trials that compared oral versus intravenous volume expansion for the prevention of radiocontrast-induced nephropathy in patients receiving arterial contrast reported no significant difference in the risk of contrast induced acute kidney injury between the oral and intravenous arms. Most trials for contrast nephropathy prevention have been in the setting of arterial contrast such as with cardiac catheterization, and not with venous contrast, such as computed tomography. The aim of this paper is to describe the protocol of a pilot trial comparing the effect of oral salt and water versus intravenous saline on the prevention of Acute Kidney Injury following contrast-enhanced computed tomography. Methods Our study is a pilot, single-centre parallel randomized controlled trial. To be included, participants must be at stage 4 of chronic kidney disease as defined by a glomerular filtration rate <30 mL/min/1.73 m2, aged greater than 18 years and to undergo an outpatient contrast-enhanced computer tomography of the chest or abdomen. A total 50 patients will be randomised to receive either oral salt and water or intravenous isotonic saline. The primary outcome is feasibility, including estimates of recruitment rate, adherence to intervention and completeness of follow-up to assist in planning the definitive trial. The secondary outcome is safety and includes adverse events with oral salt and water loading as compared to intravenous isotonic saline. Discussion The results of this pilot trial will provide critical information to plan a definitive trial to test the efficacy of the route of volume loading regimens in prevention of acute kidney injury after contrast-enhanced CT scans. Trial registration The trial is registered at the US National Institutes of Health (ClinicalTrials.gov) # NCT02084771 .